Colonic microbiota can promote rapid local improvement of murine colitis by thioguanine independently of T lymphocytes and host metabolism. Issue 1 (13th July 2016) - Oancea, I; Movva, R; Das, I; Aguirre de Cárcer, D; Schreiber, V; Yang, Y; Purdon, A; Harrington, B; Proctor, M; Wang, R; Sheng, Y; Lobb, M; et al.
Abstract : Objective: Mercaptopurine (MP) and pro-drug azathioprine are 'first-line' oral therapies for maintaining remission in IBD. It is believed that their pharmacodynamic action is due to a slow cumulative decrease in activated lymphocytes homing to inflamed gut. We examined the role of host metabolism, lymphocytes and microbiome for the amelioration of colitis by the related thioguanine (TG). Design: C57Bl/6 mice with or without specific genes altered to elucidate mechanisms responsible for TG's actions were treated daily with oral or intrarectal TG, MP or water. Disease activity was scored daily. At sacrifice, colonic histology, cytokine message, caecal luminal and mucosal microbiomes were analysed. Results: Oral and intrarectal TG but not MP rapidly ameliorated spontaneous chronic colitis in Winnie mice (point mutation in Muc2 secretory mucin). TG ameliorated dextran sodium sulfate-induced chronic colitis in wild-type (WT) mice and in mice lacking T and B lymphocytes. Remarkably, colitis improved without immunosuppressive effects in the absence of host hypoxanthine (guanine) phosphoribosyltransferase (Hprt)-mediated conversion of TG to active drug, the thioguanine nucleotides (TGN). Colonic bacteria converted TG and less so MP to TGN, consistent with intestinal bacterial conversion of TG to so reduce inflammation in the mice lacking host Hprt. TG rapidly induced autophagic flux in epithelial, macrophage and WT but not Hprt −/− fibroblast cell lines and augmented epithelial intracellular bacterial killing. Conclusions: Treatment by TG is not necessarily dependent on the adaptive immune system. TG is a more efficacious treatment than MP in Winnie spontaneous colitis. Rapid local bacterial conversion of TG correlated with decreased intestinal inflammation and immune activation.